1999
DOI: 10.2741/a424
|View full text |Cite
|
Sign up to set email alerts
|

T cells and aging update February 1999

Abstract: T cell immunosenescence 218effects of dysregulated immune responses in the elderly by supplementation or other approaches may result in an enhancement of their quality of life, and significant reductions in the cost of medical care in old age. FACTORS CONTRIBUTING TO IMMUNO-SENESCENCE HematopoiesisDysregulated hematopoiesis is seen in elderly individuals, raising the possibility that this could contribute to altered immune function in the aged. Hematopoiesis in man may be compromised because of a severely redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 186 publications
(216 reference statements)
0
33
1
1
Order By: Relevance
“…Castration restored the responsiveness to HSV to levels equivalent to those seen in young mice, possibly relating to a restoration of the CD4:CD8 T cell ratio in the resting lymph node population (data not shown). It would be of interest to assess the function of APC in this model because these have been shown to be defective in aged mice (53), are vital for proper viral responsiveness (50), and are able to be modulated by sex steroids (54).…”
Section: Discussionmentioning
confidence: 99%
“…Castration restored the responsiveness to HSV to levels equivalent to those seen in young mice, possibly relating to a restoration of the CD4:CD8 T cell ratio in the resting lymph node population (data not shown). It would be of interest to assess the function of APC in this model because these have been shown to be defective in aged mice (53), are vital for proper viral responsiveness (50), and are able to be modulated by sex steroids (54).…”
Section: Discussionmentioning
confidence: 99%
“…In the process of aging over time, more memory cells are generated; the body has only a limited capacity of cells it can sustain and the immune system favors memory over naïve cells, which is the basis of adaptive immunity. These age-associated alterations and their consequences have been reviewed elsewhere by us Larbi et al 2008;Pawelec et al 1999) and many others. The present study found a tendency towards the presence of lower percentages of CD4+ cells and reciprocally, highly significantly more CD8+ (p < 0.0001) cells in the elderly compared to the young in a rural population of Pakistani men.…”
Section: Discussionmentioning
confidence: 99%
“…The healthy elderly have an increased proportion of memory CD4 ϩ and CD8 ϩ T cells expressing the surface marker CD45RO and a decreased proportion of naive T cells expressing CD45RA (2)(3)(4), although the absolute and relative numbers of CD4 ϩ and CD8 ϩ T cells appear to remain unchanged with aging (1). Elderly individuals have decreased T cell proliferative responses to mitogens in vitro and less IL-2 secretion from Ag-stimulated T cells compared with young people (1,5,6), perhaps related to decreased expression of CD28, a costimulatory molecule critical for T cell activation (7,8). Studies of T cell cytokine synthesis in the elderly have yielded conflicting data.…”
mentioning
confidence: 99%